Avascular Necrosis - Melina Handayani; Muhammad Bayu Rizaldy, Sp.OT (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Osteonecrosis can be defined as bone cell death resulting from impaired blood flow to the bone due to traumatic or non-traumatic events. Case Presentation: We present a case in which a 62-year-old female came to the Orthopedic Surgery Polyclinic with complaints of pain in her groin. The pain is intermittent and worsens when the patient moves his legs. This makes it difficult for patients to sit and have pain when walking, so they need a cane as a tool. This complaint has been felt for ± 1.5 years and has been getting worse since this 1 month. During the pain the patient said he was taking pain relievers but his complaints did not decrease. On local examination in the left Hip Joint region, it was found that on look examination there was no visible deformity, swelling and skin color that was the same as the surrounding area. On examination of the feel found positive tenderness. On AP pelvic X-ray examination, there was a fracture of the left femoral head with superior displacement. Treatment for this patient includes non-surgical and surgical (total hip replacement). Conclusion: The patient was diagnosed with Avascular necrosis.